Psychological Responses of Health Care Workers Are Strongly Associated With Pandemic Management - Pacutova, Veronika; Madarasova Geckova, Andrea; Kizek, Peter; Novotny, Martin; de Winter, Andrea F.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2022)
Background Globally, governments adopted protective measures to stabilise the worsening COVID-19 pandemic situation. These measures had a large impact on health care workers (HCWs) and could make the work environment more stressful for them. Therefore, we explored the associations of the psychological responses of HCWs and pandemic management among Slovak health care workers during the second wave of the pandemic. Methods We obtained data about psychological responses, COVID-19 experiences, information overload, non-adherence of the public, work stress and barriers and facilitators of health care provision from HCWs at the COVID-19-related departments of one hospital that mainly covered eastern Slovakia (215 health care professionals, 77.7% females, M/SD=44.4). Data were analysed using logistic regression models adjusted for gender. Results Pandemic management was most strongly associated with psychological responses, such as irritability, sadness, anxiety, dizziness and back pain, in health care workers. The non-adherence of the public had the strongest associated psychological impact on HCWs, mostly affecting anxiety and irritability (odds ratios, ORs varying from 3.9 to 7.0). From the barriers and facilitators of health care provision, the use of personal protective equipment had the most impact psychologically, whereas efficient department management was most protective, with ORs around 0.3. Conclusion Pandemic management has a large impact on health care workers, and promoting resilience may seriously decrease job-related stress and associated psychological responses of HCWs.